Bagaimana Perusahaan di Indonesia Mengungkapkan Perbudakan Modern? How Do Companies in Indonesia Disclose Modern Slavery? - Kautsar Nugraha, Farhani (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2023)
In some countries, new forms of disclosure regulation related to the issue of human rights and modern slavery have emerged, such as the UK Modern Slavery Act. But in Indonesia, to this day there are no regulations related to modern slavery disclosures. This paper aims to find out disclosures related to modern slavery in Indonesian companies. This paper uses content analysis as a method for analyzing reports published by companies listed on the Indonesia Stock Exchange. The companies used as samples are companies in the agriculture, construction, and textile industry sectors. In general, companies in Indonesia have disclosed some information regarding modern slavery. Even so, the quality of the information is still very low because it uses narrative or descriptive disclosure. Not much information has been disclosed quantitatively for each modern slavery sub-theme. This conclusion can be a recommendation for regulators to immediately issue regulations that require companies in Indonesia to disclose specific information related to modern slavery.